Godišnje vatre - Đaković, Branko (2006)
The customs related to the lightning of annual fires have not been systematically researched so far, and in ethnological writings related topics appear only marginally. They were mostly described as parts of customs linked to specific religious holidays (Carnival customs, St. Juraj’ s Day, Eastern, Midsummer Day, St. Peter’ s, etc.) As part of the Project that was conducted in the second half of the 20th century, with the aim to publish Ethnological Atlas of Europe, the Center for Ethnological Cartography of, then existing, the Union of Ethnological Associations of Yugoslavia, started a large scale project of collecting field material. One of the topics covered in the research were the Annual Fires. On the sample of 2400 villages, this article tries to systematize and analyze data on the distribution of this custom and its various names (kres, vatra, oganj, lila – olalija, koleda, karaveštica, orta kopa – oratnica...). The article also analyses ethnological maps and tables with commentaries, as well as some contemporary customns and rituals which have contributed to the folklorisation of this custom with the manifestations which supplement original traditional elements.
ENG